Preparation method of high-anti-reflection periodic structure on diamond surface
The preparation of two-dimensional periodic columnar structures on the diamond surface by femtosecond laser induced, solving the problem of low optical window transmittance in diamond materials, and achieving improvement of optical transmittance and structural stability and durability.
Patent Information
- Application Number
- CN202510077305.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-25
AI Technical Summary
The optical transmittance of diamond material optical windows is low, and traditional amphipathic film technology has shortcomings in terms of stability and durability.
A two-dimensional periodic columnar structure was prepared on the diamond surface by femtosecond laser induced, and a solid nanostructure was formed by orthogonal cross-scanning method to improve optical transmittance.
The optical transmittance of diamond crystals is improved by about 20%, and the stability and damage resistance of the structure are improved.
Smart Images

Figure CN119882103A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of optical material preparation, and in particular relates to the preparation of a diamond periodic surface structure. Background Art
[0002] Traditional optical anti-reflection technology achieves the anti-reflection effect by coating one or more layers of thin films on the surface of optical components. Such films are usually composed of materials with different refractive indices. The interference effect of the multilayer films reduces the reflection of light, thereby improving the transmittance. Specifically, the principle of anti-reflection film is based on the interference phenomenon of light waves. By precisely controlling the thickness and refractive index of the film layer, the phase difference of light of different wavelengths when reflected and transmitted on the surface of the film layer is offset, thereby reducing the intensity of the reflected light and achieving the effect of improving the transmittance. However, there are some disadvantages in the practical application of traditional anti-reflection film technology, which are mainly reflected in the stability and durability of the film layer. First, the thin film used in the coating process is usually fragile and easily affected by the external environment, such as temperature changes, humidity, mechanical collisions, etc., causing the film layer to fall off or be damaged. Such film shedding or damage will not only significantly reduce the anti-reflection effect, but may also affect the service life and performance of the optical component. Secondly, the weather resistance and scratch resistance of the coating material are also limited. During long-term use, the film layer may be worn, oxidized or aged, thereby affecting its performance.
[0003] Patent publication number CN111168233A discloses a method for picosecond laser-induced periodic structure on the surface of optical glass, specifically: a picosecond laser beam is focused on the surface of the optical glass through a beam expansion and focusing device, and after 1-20 pulses, LIPSS is formed on the surface. The prepared LIPSS can change the optical properties of the glass, reduce the surface reflectivity and increase the transmittance. However, at present, although it is disclosed that a large-area periodic structure can be prepared by using a line spot, the substrates acted on are mostly glass, semiconductor materials and alloy materials. There are few studies on the rapid preparation of laser-induced periodic surface structures (LIPSS) on diamond surfaces with higher hardness, and the effect of changes in periodic surface structures on their transmittance is more complicated. Especially for diamond materials for optical windows with higher transmittance requirements, their periodic surface structures are expected to further improve their transmittance enhancement. Summary of the invention
[0004] In response to the technical problem of low optical transmittance of optical windows of diamond materials, the present invention proposes a method for preparing a high anti-reflection periodic structure on the surface of diamond, which achieves the anti-reflection effect by inducing a more solid nanostructure on the surface of the material, so as to improve the stability, durability and damage resistance of the optical element. The optical transmittance of the prepared diamond crystal is increased by 20% compared with the intrinsic surface.
[0005] In order to achieve the above object, the technical solution of the present invention is achieved as follows:
[0006] A method for preparing a diamond surface high anti-reflection periodic structure comprises the following steps:
[0007] (1) The femtosecond laser is converted into a line spot after passing through a cylindrical lens and an objective lens and is focused on the surface of the diamond sample (the defocus distance is 0). The line spot first moves in a direction perpendicular to the laser polarization, inducing a one-dimensional periodic stripe structure.
[0008] (2) Subsequently, an orthogonal cross scanning method is used, whereby the line light spot is moved perpendicularly to the one-dimensional periodic stripe structure to prepare a two-dimensional periodic columnar structure;
[0009] (3) Cleaning the two-dimensional periodic columnar structure.
[0010] The wavelength of the femtosecond laser is 400-1200nm, the repetition frequency is 10-50kHz, and the pulse width is 50-500fs.
[0011] The wavelength of the femtosecond laser is 515 nm, the repetition frequency is 25 kHz, and the pulse width is 378 fs.
[0012] The focal length of the cylindrical lens is 10-15 cm.
[0013] The numerical aperture of the objective lens is 0.7, and the magnification of the objective lens is 60 times.
[0014] The length of the line spot is 20-25 μm.
[0015] In the step (1), the power of the line spot is 12-18 mW, the scanning speed is 0.1 mm / s, and the exposure time is 500-1000 μs.
[0016] In the step (2), the power of the line spot is 8-25 mW, the scanning speed is 0.01-0.2 mm / s, the exposure time is 500-1000 μs, the attenuation plate angle is 0-60°, and the defocus distance is 0-1 μm.
[0017] Preferably, in step (2), the power of the line spot is 10-25 mW, the scanning speed is 0.04-0.16 mm / s, the exposure time is 500-1000 μs, the attenuation plate angle is 10-60°, and the defocus distance is 0.2-0.8 μm.
[0018] The cleaning in step (3) is performed by wet etching.
[0019] The wet etching solution includes concentrated sulfuric acid and concentrated nitric acid in a volume ratio of (6-10):1.
[0020] Beneficial effects of the present invention: The LIPSS prepared by the present invention is a two-dimensional periodic columnar structure. Since it has periodicity in two directions, it is found through optical performance tests that the optical transmittance of the diamond crystal with LIPSS is 20% higher than that of the intrinsic surface. The anti-reflection effect is achieved, and the structural stability is good. In addition, during the cross-scanning process, the periodic structures in two different directions may produce a certain degree of overlap or resonance effect, which may enhance the depth of the structure. For example, when the periodic patterns in two directions interact with each other, a certain degree of resonance mode may be formed, which makes the removal or reshaping of the surface material more significant, further deepening the depth of the periodic columnar structure. At the same time, the two-dimensional columnar structure can achieve a smoother refractive index change gradient than the one-dimensional stripe structure, and is therefore better than the one-dimensional stripe structure in terms of anti-reflection effect. Therefore, the columnar structure of the present invention also has a better anti-reflection effect than the stripe structure. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0022] Figure 1 (a) Schematic diagram of the optical path for efficient preparation of large-area LIPSS structures using line spots; Figure 1 (b) is the line spot CCD photo.
[0023] Figure 2 Schematic diagram of the preparation of two-dimensional periodic columnar structure for orthogonal scanning.
[0024] Figure 3 This is a scanning electron microscope photograph of the horizontal stripe structure at a magnification of 10,000 times.
[0025] Figure 4 This is a scanning electron microscope photograph of the horizontal stripe structure at a magnification of 60,000 times.
[0026] Figure 5 This is a scanning electron microscope photograph of the two-dimensional columnar structure before cleaning.
[0027] Figure 6 This is a scanning electron microscope photo of the two-dimensional columnar structure after cleaning and magnified 30,000 times.
[0028] Figure 7 This is a scanning electron microscope photo of the two-dimensional columnar structure after cleaning and magnified 60,000 times.
[0029] Figure 8This is a scanning electron microscope photo of the two-dimensional columnar structure after cleaning and magnified 240,000 times.
[0030] Fig. 9 SEM photos of LIPSS structure at different attenuation plate angles: (a) 60°; (b) 50°; (c) 40°; (d) 30°; (e) 20°; and (f) 10°.
[0031] Fig.10 SEM photos of LIPSS structures at different scanning speeds: (a) 0.01 mm / s; (b) 0.04 mm / s; (c) 0.08 mm / s; (d) 0.12 mm / s; (e) 0.16 mm / s; (f) 0.2 mm / s.
[0032] Fig.11 SEM photos of LIPSS structures at different focusing positions: (a) defocus 1 μm; (b) defocus 0.8 μm; (c) defocus 0.6 μm; (d) defocus 0.4 μm; (e) defocus 0.2 μm; (f) 0 μm;
[0033] Fig.12 Comparison of the optical transmittance of different structures and intrinsic diamonds as a function of incident wavelength
[0034] Fig.13 AFM comparison of stripe structure and columnar structure. DETAILED DESCRIPTION
[0035] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] The femtosecond laser is generated by a femtosecond laser micro-nano processing system, which generally includes an ultrafast femtosecond laser light source, a light field modulation device, a three-dimensional nano-processing system and a real-time imaging observation system. The generation and adjustment of the femtosecond laser have been widely disclosed in the prior art, and those skilled in the art can make adjustments as needed.
[0037] The femtosecond laser micro-nano processing system of the following embodiment is as follows Figure 1As shown in (a), the processing system is mainly composed of a femtosecond laser, a transmission optical path system, a half-wave plate, an attenuation plate, and a galvanometer control system built on a stable optical platform. The laser is focused onto the surface of the sample to be processed through the objective lens. The sample to be processed is placed on the piezoelectric displacement platform. The energy and polarization direction of the laser can be adjusted in real time by adjusting the attenuation plate and the half-wave plate. The processing process can be observed in real time through the CCD imaging system. The main devices will be introduced in detail below.
[0038] (1) Femtosecond laser and frequency doubling system
[0039] The femtosecond laser light source used is a fiber laser produced by Wuhan Anyang Laser Company. The laser output pulse width is 378fs, the central wavelength is 1035.32nm, the power stability is 0.08%, the spot diameter is 3.198mm in the X-axis direction, 2.972mm in the Y-axis direction, the spot circularity is 92.9%, and the pulse repetition rate is tunable from 25kHz to 50MHz. The original laser passes through a barium metaborate crystal and the frequency is doubled to 515nm to obtain higher processing accuracy. The parameter adjustment of the femtosecond laser is realized through the control software in the computer.
[0040] (2) CCD real-time observation system
[0041] The laser is focused on the surface of the processed sample through the objective lens, and the light signal with sample information is returned to the CCD through reflection from the material surface. This process is realized through the control software of the CCD real-time monitoring system installed in the computer, so that the entire experimental processing system can be accurately controlled and the surface information of the processed material can be observed in real time.
[0042] (3) Galvanometer system and piezoelectric platform
[0043] In order to achieve precise positioning of samples at the nanoscale, the scanning galvanometer system of Century Sunny and the piezoelectric displacement platform of Core Tomorrow are used. During the processing, the galvanometer controls the movement of the laser in the XY direction by changing the laser deflection angle, with a maximum scanning speed of 20mm / s and a scanning range of 120μm×120μm; the piezoelectric platform controls the movement of the sample stage in the Z direction, with a stroke of 100μm and a resolution of 1nm. The piezoelectric platform, galvanometer system and the on and off status of the laser can be integrated and controlled through the Maleon Fab software.
[0044] Femtosecond laser is shaped into a line spot by a cylindrical lens. Femtosecond laser pulse shaping technology refers to the technology of generating almost any desired light wave pulse shape by controlling the amplitude, phase and polarization direction of femtosecond laser pulses. It is mainly divided into time domain shaping and space domain shaping. A cylindrical lens is a lens with different radii on the X-axis and Y-axis, which is widely used for one-dimensional shaping of light sources. They have two structures, flat-concave and flat-convex, which are used to diverge or converge light beams respectively. It is generally used to focus the incident light onto a line or change the aspect ratio of an image. The cylindrical mirror has a cylindrical surface that enables the incident light to be focused on a certain dimension and stretch the image. The focal length of the cylindrical mirror can be negative or positive, which is suitable for laser line generation or deformed beam shaping to circularize the laser output. In the following embodiments, a cylindrical lens is added to a femtosecond laser micro-nano processing system, and a combination of a cylindrical lens and an objective lens is used to ultimately generate a line spot.
[0045] Example 1
[0046] A method for preparing a diamond surface high anti-reflection periodic structure, such as Figure 2 As shown, first prepare one-dimensional periodic stripes and then orthogonally scan to prepare a two-dimensional periodic columnar structure. The specific steps are as follows:
[0047] The first step is the preparation and fixation of the target sample
[0048] The diamond sample was ultrasonically cleaned in deionized water to obtain a pre-processed sample, and then the pre-processed sample was fixed on a three-dimensional precision mobile platform in an air environment. During the processing, the galvanometer controls the movement of the laser in the XY direction by changing the laser deflection angle, with a maximum scanning speed of 20mm / s and a scanning range of 120μm×120μm; the piezoelectric platform controls the movement of the sample stage in the Z direction, with a stroke of 100μm and a resolution of 1nm. The piezoelectric platform, galvanometer system, and the on and off status of the laser can be integrated and controlled through the Maleon Fab software.
[0049] The second step is to obtain high-precision vertically polarized femtosecond laser
[0050] The original laser output pulse width is 378fs, the central wavelength is 1035.32nm, the power stability is 0.08%, the spot diameter is 3.198mm in the X-axis direction, 2.972mm in the Y-axis direction, the spot circularity is 92.9%, and the pulse repetition rate is 25kHz. The original laser is doubled to 515nm through a barium metaborate crystal to obtain higher processing accuracy. A polarizer and a half-wave plate combination mirror are added after the frequency-doubling crystal to adjust the polarization direction of the laser to vertical polarization.
[0051] The third step is to use a combination of a cylindrical lens and an objective lens, wherein the focal length of the cylindrical lens is 12 cm, the numerical aperture of the objective lens is 0.7, and the magnification of the objective lens is 60 times. Finally, a linear light spot is generated. Figure 1 (b) shows the spot shape under the CCD lens.
[0052] In the fourth step, the galvanometer system was used to perform horizontal scanning on the diamond sample (without attenuation plate), with a laser power of 14.2 mW, a scanning speed of 0.1 mm / s, and an exposure time of 1000 μs, so that the scanning direction and the polarization direction were perpendicular to each other, inducing horizontal stripes, such as Figure 3 and 4 shown.
[0053] In the fifth step, the diamond crystal is rotated 90 degrees clockwise, and the previous steps are repeated to focus the light spot on the diamond sample. The laser power of the laser scanning process is 9.7 mW, the scanning speed is 0.1 mm / s, the exposure time is 1000 μs, the attenuation angle is 50°, and the laser defocus distance is 0.4 μm. On the basis of the originally induced one-dimensional stripes, a galvanometer system is used to perform horizontal scanning so that the scanning direction and the polarization direction are perpendicular, so that the two scanning directions and the polarization direction of the light are both perpendicular. The preparation of the periodic structure is as follows Figure 5 shown.
[0054] The sixth step is to immerse the diamond sample in a mixed solution of concentrated sulfuric acid and concentrated hydrochloric acid with a volume ratio of 8:1 and continuously corrode at 80°C for 8 hours. The residual debris and impurities on the surface are removed by etching, thereby effectively reducing the surface roughness and improving the surface quality of LIPSS. Figure 6-8 As shown, both the debris in large areas and the small particles attached to the local structure have been completely removed, revealing a complete and uniform columnar structure on the surface.
[0055] Example 2
[0056] A method for preparing a diamond surface high anti-reflection periodic structure, the specific steps are as follows:
[0057] The first step is the preparation and fixation of the target sample
[0058] The diamond sample is ultrasonically cleaned in deionized water to obtain a pre-processed sample, and then the pre-processed sample is fixed on a three-dimensional precision moving platform in an air environment.
[0059] The second step is to obtain high-precision vertically polarized femtosecond laser
[0060] The original laser output pulse width is 378fs, the central wavelength is 1035.32nm, the power stability is 0.08%, the spot diameter is 3.198mm in the X-axis direction, 2.972mm in the Y-axis direction, the spot roundness is 92.9%, and the pulse repetition rate is 25kHz. The original laser passes through a barium metaborate crystal and the frequency is doubled to 515nm, so as to obtain higher processing accuracy.
[0061] The third step is to use the combination of cylindrical lens and objective lens to finally produce a linear light spot.
[0062] The fourth step is to use the galvanometer system to perform horizontal scanning on the diamond sample, with a laser power of 18 mW, a scanning speed of 0.1 mm / s, and an exposure time of 1000 μs, so that the scanning direction and the polarization direction are perpendicular to each other, inducing horizontal stripes.
[0063] The fifth step is to rotate the diamond crystal 90 degrees clockwise and repeat the previous steps to focus the light spot on the diamond sample. The laser power of the laser scanning process is 25mW, the scanning speed is 0.1mm / s, the exposure time is 1000μs, the attenuation angle is 50°, and the laser defocus distance is 0.4μm. Based on the originally induced one-dimensional stripes, a galvanometer system is used to perform horizontal scanning to make the scanning direction and the polarization direction perpendicular, so that the two scanning directions and the polarization direction of the light are both perpendicular.
[0064] In the sixth step, the diamond sample was immersed in a mixed solution of concentrated sulfuric acid and concentrated hydrochloric acid in a volume ratio of 8:1, and the corrosion was continued at 80°C for 8 hours.
[0065] Example 3
[0066] The difference from Example 2 is that in step 5, the angle of the attenuation plate is 60°, and the other steps are the same.
[0067] Example 4
[0068] The difference from Example 2 is that in step 5, the angle of the attenuation plate is 40°, and the other steps are the same.
[0069] Example 5
[0070] The difference from Example 2 is that in step 5, the angle of the attenuation plate is 30°, and the other steps are the same.
[0071] Example 6
[0072] The difference from Example 2 is that in step 5, the angle of the attenuation plate is 20°, and the other steps are the same.
[0073] Example 7
[0074] The difference from Example 2 is that in step 5, the angle of the attenuation plate is 10°, and the other steps are the same.
[0075] Fig. 9SEM photos of two-dimensional columnar structures under different laser powers are shown, and Figures (af) correspond to Examples 3, 2, 4, 5, 6, and 7 respectively. It can be seen from the figure that when the attenuation plate is set to 60 degrees, most of the intersection areas still present a one-dimensional stripe structure due to the low laser power, and only individual areas successfully induce a columnar structure. As the angle of the attenuation plate is adjusted to 50 degrees, the system begins to induce a gourd string structure in a semi-connected state. Further reducing the angle of the attenuation plate to 40, the connectivity of the gourd string structure gradually increases. Finally, when the angle of the attenuation plate is further reduced to 30, the gourd string structure in the semi-connected state is completely connected, forming a shorter longitudinal stripe-like molten structure. The low laser power leads to insufficient local thermal effect of the laser on the diamond material, making it difficult to induce secondary induction, showing a relatively single one-dimensional stripe. When the angle of the attenuation plate is reduced to 20 degrees, the laser power increases, the thermal effect is enhanced, the local melting of the material is more sufficient, and the generation and connection of the gourd string structure are promoted. As the angle of the attenuation plate decreases to 10 degrees, the thermal effect becomes more significant, the gourd string structure gradually merges, and finally forms a shorter longitudinal stripe-like molten structure.
[0076] Example 8
[0077] The difference from Example 2 is that the scanning speed in step 5 is 0.01 mm / s, and the other steps are the same.
[0078] Example 9
[0079] The difference from Example 2 is that the scanning speed in step 5 is 0.04 mm / s, and the other steps are the same.
[0080] Example 10
[0081] The difference from Example 2 is that the scanning speed in step 5 is 0.08 mm / s, and the other steps are the same.
[0082] Embodiment 11
[0083] The difference from Example 2 is that the scanning speed in step 5 is 0.12 mm / s, and the other steps are the same.
[0084] Example 12
[0085] The difference from Example 2 is that the scanning speed in step 5 is 0.16 mm / s, and the other steps are the same.
[0086] Embodiment 13
[0087] The difference from Example 2 is that the scanning speed in step 5 is 0.20 mm / s, and the other steps are the same.
[0088] Fig.10SEM photos of two-dimensional columnar structures at different scanning speeds are shown, and Figures (af) correspond to Examples 8-13 in turn. As can be seen from the figure, when the scanning speed is 0.01mm / s, the spot overlap rate is too high, resulting in the melting of the columnar structure and the evolution into longitudinal stripes; when the scanning speed is 0.04mm / s, the columnar structure increases significantly, but the uniformity of the structure is poor, and a few columnar structures are destroyed by melting. When the scanning speed is increased to 0.08mm / s, a relatively neat columnar structure appears, but these structures are scattered in the sheet area and fail to form a continuous area. When the scanning speed is further increased to 0.12mm / s, the entire scanning area can successfully induce a two-dimensional structure. However, although the structure is generated more uniformly, the uniformity and uniformity still do not reach the expected ideal state. When the scanning speed continues to increase, some areas fail to induce a columnar structure, but retain a one-dimensional striped morphology. It is worth noting that cracks appear in some stripes, which may be related to the excessively high scanning speed, resulting in insufficient local heat transfer, which cannot maintain the integrity of the columnar structure.
[0089] Embodiment 14
[0090] The difference from Example 2 is that in step 5, the laser defocus distance is 1 mm / s, and the other steps are the same.
[0091] Embodiment 15
[0092] The difference from Example 2 is that in step 5, the laser defocus distance is 0.8 mm / s, and the other steps are the same.
[0093] Example 16
[0094] The difference from Example 2 is that in step 5, the laser defocus distance is 0.6 mm / s, and the other steps are the same.
[0095] Embodiment 17
[0096] The difference from Example 2 is that in step 5, the laser defocus distance is 0.2 mm / s, and the other steps are the same.
[0097] Embodiment 18
[0098] The difference from Example 2 is that in step 5, the laser defocus distance is 0 mm / s, and the other steps are the same.
[0099] Fig.11SEM photos of two-dimensional columnar structures at different defocus distances are shown, and Figures (af) correspond to Examples 14, 15, 16, 2, 17, and 18, respectively. It can be seen from the figure that when the defocus position is 1 μm, the laser beam fails to be fully focused, resulting in some areas not being sufficiently irradiated by the laser, so the expected columnar structure cannot be formed, and these areas retain the original stripe morphology without morphological changes. When the defocus position is 0.8 μm, the induced columnar structure exhibits relatively uneven characteristics, the size differences of some columnar structures are large, and the cracks between the structures are of different widths, showing strong non-uniformity. This shows that slight defocusing can lead to unstable morphology of the structure and may affect the regularity of the structure. When the defocus position is 0.6 μm, the obtained columnar structure is neat and uniform, but the scanning electron microscope (SEM) image shows that some columnar structures appear brighter, while others are darker, indicating that there are differences in the height of the columns. Although the overall neatness of the structure is guaranteed, there are still certain height differences. This may be due to the fact that the focus accuracy is not fully optimized, resulting in uneven distribution of laser energy in different areas. As the defocus position is 0.4μm, the brightness of the columnar structure becomes more uniform, and the neatness is significantly improved, showing a clearer columnar outline. However, when the focus is over-focused, the outline of the columnar structure gradually blurs, the shape becomes less obvious, and a more blurred structure is presented. After further deepening the focus, the structure changes from a neat columnar shape to an irregular spherical shape, indicating that excessive focusing of the laser beam causes excessive melting or re-solidification of the material, ultimately destroying the morphology of the columnar structure.
[0100] Comparative Example 1
[0101] A method for preparing a diamond surface high anti-reflection periodic structure, the specific steps are as follows:
[0102] The first step is the preparation and fixation of the target sample
[0103] The diamond sample is ultrasonically cleaned in deionized water to obtain a pre-processed sample, and then the pre-processed sample is fixed on a three-dimensional precision moving platform in an air environment.
[0104] The second step is to obtain high-precision vertically polarized femtosecond laser
[0105] The original laser output pulse width is 378fs, the central wavelength is 1035.32nm, the power stability is 0.08%, the spot diameter is 3.198mm in the X-axis direction, 2.972mm in the Y-axis direction, the spot roundness is 92.9%, and the pulse repetition rate is 25kHz. The original laser passes through a barium metaborate crystal and the frequency is doubled to 515nm, so as to obtain higher processing accuracy.
[0106] The third step is to use the combination of cylindrical lens and objective lens to finally produce a linear light spot.
[0107] The fourth step is to use the galvanometer system to perform horizontal scanning on the diamond sample, with a laser power of 18 mW, a scanning speed of 0.1 mm / s, and an exposure time of 1000 μs, so that the scanning direction and the polarization direction are perpendicular to each other, inducing horizontal stripes.
[0108] The fifth step is to immerse the diamond sample in a mixed solution of concentrated sulfuric acid and concentrated hydrochloric acid in a volume ratio of 8:1, and continuously corrode at 80°C for 8 hours.
[0109] Fig.12 The transmittance test of the columnar diamond prepared in Example 2, the stripe diamond in Comparative Example 1 and the untreated intrinsic diamond shows that the transmittance of the columnar diamond prepared in Example 2 shows a parabolic upward trend in the process of improving the transmittance enhancement effect. In the band of 600nm to 700nm, the transmittance of the prepared two-dimensional columnar periodic structure is as high as more than 90%, which is more than 20% higher than that of intrinsic diamond, and 15% higher than that of the traditional stripe structure. This new preparation method not only improves the optical properties of the diamond surface, but also provides new ideas for the design and application of future optical devices, especially in the fields requiring high transmittance and high optical quality, and has broad application prospects.
[0110] Subsequently, the differences between the two were further analyzed, and the three-dimensional graph of the atomic force test ( Fig.13 ), an area was selected, including a one-dimensional stripe structure and a two-dimensional columnar structure. It can be clearly observed that the two-dimensional columnar structure is deeper than the one-dimensional stripe structure. During the cross-scanning process, the periodic structures in two different directions may produce a certain degree of overlap or resonance effect, which may enhance the depth of the structure. For example, when the periodic patterns in two directions interact with each other, a certain degree of resonance mode may be formed, which makes the removal or reshaping of the surface material more significant, further deepening the depth of the periodic columnar structure.
[0111] The duty cycle of the structure (i.e., the ratio of the raised portion to the overall structural period) has a complex effect on the anti-reflection effect. The duty cycle not only determines the band width and peak size of the anti-reflection, but also has a significant impact on the optical performance of the structure at different incident angles. Especially under large-angle incidence conditions, changes in the duty cycle can lead to significant differences in the anti-reflection effect. Therefore, a reasonable design of the duty cycle is one of the keys to optimizing the performance of subwavelength anti-reflection structures. In general, the synergistic effect between the period, height, and duty cycle determines the optical performance of the subwavelength anti-reflection structure, and in different application scenarios, precise adjustment of the combination of these parameters can achieve the best anti-reflection effect.
[0112]
[0113] Where nair and ns are the refractive indices of air and material respectively, and h is the minimum value for achieving anti-reflection effect. According to anti-reflection theory, light will refract when passing through the boundary of different media, and the change of refraction angle and refractive index is described by the law of refraction (Snell's law). For diamond materials, which have a higher refractive index, the refraction and reflection phenomena that occur when light enters diamond from air (lower refractive index) are the research focus of anti-reflection technology. By precisely designing the shape of micro-nano structures (such as periodic nanostructures, micron columns, conical structures, etc.), the reflected light and the transmitted light can interfere in phase, thereby eliminating part of the reflection and enhancing the transmittance. For example, when the structure is properly designed, the phase difference between the reflected light and the incident light can make the reflected light cancel each other and enhance the intensity of the transmitted light. The design goal is to improve the transmittance and enhance the optical properties of the material by changing the propagation path of light or reducing reflection. Compared with the one-dimensional stripe structure, the two-dimensional columnar structure can achieve a smoother refractive index change gradient, so it is better than the one-dimensional stripe structure in anti-reflection effect.
[0114] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a diamond surface high anti-reflection periodic structure, characterized in that: The following steps are involved: (1) The femtosecond laser is converted into a line spot after passing through a cylindrical lens and an objective lens and is focused on the surface of the diamond sample. The line spot first moves in a direction perpendicular to the laser polarization, inducing a one-dimensional periodic stripe structure. (2) Subsequently, an orthogonal cross scanning method is used, whereby the line light spot is moved perpendicularly to the one-dimensional periodic stripe structure to prepare a two-dimensional periodic columnar structure; (3) Cleaning the two-dimensional periodic columnar structure.
2. The method for preparing the diamond surface high anti-reflection periodic structure according to claim 1, characterized in that: The wavelength of the femtosecond laser is 400-1200nm, the repetition frequency is 10-50kHz, and the pulse width is 50-500fs.
3. The method for preparing the diamond surface high anti-reflection periodic structure according to claim 2, characterized in that: The wavelength of the femtosecond laser is 515 nm, the repetition frequency is 25 kHz, and the pulse width is 378 fs.
4. The method for preparing a diamond surface high anti-reflection periodic structure according to any one of claims 1 to 3, characterized in that: The focal length of the cylindrical lens is 10-15 cm.
5. The method for preparing a diamond surface high anti-reflection periodic structure according to claim 4, characterized in that: The numerical aperture of the objective lens is 0.7, and the magnification of the objective lens is 60 times.
6. The method for preparing a diamond surface high anti-reflection periodic structure according to claim 5, characterized in that: The length of the line spot is 20-25 μm.
7. The method for preparing a diamond surface high anti-reflection periodic structure according to claim 6, characterized in that: In the step (1), the power of the line spot is 12-18 mW, the scanning speed is 0.01-0.2 mm / s, and the exposure time is 500-1000 μs.
8. The method for preparing a diamond surface high anti-reflection periodic structure according to claim 7, characterized in that: In the step (2), the power of the line spot is 8-25 mW, the scanning speed is 0.01-0.2 mm / s, the exposure time is 500-1000 μs, the attenuation plate angle is 0-60°, and the defocus distance is 0-1 μm.
9. The method for preparing a diamond surface high anti-reflection periodic structure according to claim 8, characterized in that: The cleaning in step (3) is performed by wet etching.
10. The method for preparing a diamond surface high anti-reflection periodic structure according to claim 9, characterized in that: The wet etching solution includes concentrated sulfuric acid and concentrated nitric acid in a volume ratio of (6-10):1.
Citation Information
Patent Citations
Method for inducing periodic structure on surface of optical glass by picosecond laser
CN111168233A
Method for preparing large-area periodic structure through linear light spot induction
CN107498183A
Diamond mid-infrared optical window with anti-reflection microstructure and preparation method of diamond mid-infrared optical window
CN119105118A
Processing method of period-adjustable micro-nano oxidation periodic structure
CN119282407A
Method for forming cyclic microstructure by femtosecond laser irradiation
JP2003057422A